Odpowiedzi

Najlepsza Odpowiedź!
2010-02-18T19:34:32+01:00
1
2x+2y-x+y=4
3x-6y+4x+4y=5

x+3y=4
7x-2y=5

x=4-3y
7(4-3y)-2y=5

x=4-3y
28-21y-2y=5

x=4-3y
y=1

x=1
y=1

2

3(x+y)-2(x-2y)=5
2(x+2)-4(y+1)= -8

3x+3y-2x+4y=5
2x+4-4y-4=-8

x+7y=5
2x-4y=-8

x=5-7y
2(5-7y)-4y=-8

x=5-7y
10-14y-4y=-8

x=5-7y
-18y=-18

x=-2
y=1

3
4(x+2y)-3(x-y)=42
2(y-x)+3(x-y)=-6

4x+8y-3x+3y=42
2y-2x+3x-3y=-6

x+11y=42
x-y=-6

y-6+11y=42
x=y-6

12y=48
x=y+6

y=4
x=y+6

y=4
x=10

4
2(3x+4y)-7(y-x)=-37
4(x+2)-(y-4)=-2

6x+8y-7y+7x= -37
4x+8-y+4= -2

13x+y=-37
4x-y=-14

13x+4x+14=-37
y=4x+14

17x=-51
y=4x+14

x=-3
y=4*(-3)+14

x=-3
y=2
  • Użytkownik Zadane
2010-02-18T21:27:04+01:00
1
2x+2y-x+y=4
3x-6y+4x+4y=5

x+3y=4
7x-2y=5

x=4-3y
7(4-3y)-2y=5

x=4-3y
28-21y-2y=5

x=4-3y
y=1

x=1
y=1

2

3(x+y)-2(x-2y)=5
2(x+2)-4(y+1)= -8

3x+3y-2x+4y=5
2x+4-4y-4=-8

x+7y=5
2x-4y=-8

x=5-7y
2(5-7y)-4y=-8

x=5-7y
10-14y-4y=-8

x=5-7y
-18y=-18

x=-2
y=1

3
4(x+2y)-3(x-y)=42
2(y-x)+3(x-y)=-6

4x+8y-3x+3y=42
2y-2x+3x-3y=-6

x+11y=42
x-y=-6

y-6+11y=42
x=y-6

12y=48
x=y+6

y=4
x=y+6

y=4
x=10

4
2(3x+4y)-7(y-x)=-37
4(x+2)-(y-4)=-2

6x+8y-7y+7x= -37
4x+8-y+4= -2

13x+y=-37
4x-y=-14

13x+4x+14=-37
y=4x+14

17x=-51
y=4x+14

x=-3
y=4*(-3)+14

x=-3
y=2
2010-02-18T21:34:43+01:00
2(x+y)-(x-y)=4
3(x-2y)+4(x+y)=5

2x+2y-x+y=4
3x-6y+4x+4y=5

x=4-3y
7x-2y=5

7(4-3y)-2y=5
x=4-3y

28-21y-2y=5
x=4-3y

-23y=23
x=4-3y

y=-1
x=4-3y

y=-1
x=4-3 x (-1)

y=-1
x=4-(-3)

y=-1
x=1
2.
3(x+y)-2(x-2y)=5
2(x+2)-4(y+1)=-8

3x+3y-2x+4y=5
2x+4-4y-4=-8

x=5-7y
2x-4y=-8

x=5-7y
2(5-7y)-4y=-8

x=5-7y
10-14y-4y=-8

x=5-7y
-18y=-18

x=5-7y
y=1

x=5-7 x 1
y=1

y=1
x=-2
3.
4(x+2y)-3(x-y)=42
2(y-x)+3(x-y)=-6

4x+8y-3x+3y=42
2y-2x+3x-3y=-6

x=42-11y
-y+1(42-11y)=-6

x=42-11y
-y+42-11y=-6

x=42-11y
-12y=-48

x=42-11y
y=4

x=42-11 x 4
y=4

x=42-44
y=4

x=-2
y=4
4.
2(3x+4y)-7(y-x)=-37
4(x+2)-(y-4)=-2

6x+8y-7y+7x=-37
4x+8-y+4=-2

y=-37-13x
4x-(-37-13x)=-2-12

y=-37-13x
4x+37+13x=-14

y=-37-13x
17x=-51

y=-37-13x
x=-3

y=-37-13 x (-3)
x=-3

y=-37+39
x=-3

y=2
x=-3